De las mediaciones consentidas a las mediaciones deseadas. Lo masivo y lo colectivo en los procesos de comunicación - Luque, Beatriz; Encina, Javier (Mediaciones Sociales, 2008)
The model of communicative transformation must face the mediations imposed as representations of reality that colonize everyday life and demand the conception of Communications as collective and desired construction of the social mediations. This would imply the deconstruction of the institutional and massive features that keep the coherence of the symbolic universes and weaken the alter-natives that might make social change possible. This model considers the imposed mediations to unveil the existence of multidirectional communications processes, which are essential exchange and transformation spaces in the collective construction of social reality, enabling the desired mediations to counteract the overcrowding effect of the consented representations.